Long‐term decision regret after post‐prostatectomy image‐guided intensity‐modulated radiotherapy. Issue 1 (16th August 2016) - Shakespeare, Thomas P; Chin, Stephen; Manuel, Lucy; Wen, Shelly; Hoffman, Matthew; Wilcox, Shea W; Aherne, Noel J
Abstract: Introduction: Decision regret (DR) may occur when a patient believes their outcome would have been better if they had decided differently about their management. Although some studies investigate DR after treatment for localised prostate cancer, none report DR in patients undergoing surgery and post‐prostatectomy radiotherapy. We evaluated DR in this group of patients overall, and for specific components of therapy. Methods: We surveyed 83 patients, with minimum 5 years follow‐up, treated with radical prostatectomy (RP) and post‐prostatectomy image‐guided intensity‐modulated radiotherapy (IG‐IMRT) to 64–66 Gy followingwww.EviQ.org.au protocols. A validated questionnaire identified DR if men either indicated that they would have been better off had they chosen another treatment, or they wished they could change their mind about treatment. Results: There was an 85.5% response rate, with median follow‐up post‐IMRT 78 months. Adjuvant IG‐IMRT was used in 28% of patients, salvage in 72% and ADT in 48%. A total of 70% of patients remained disease‐free. Overall, 16.9% of patients expressed DR for treatment, with fourfold more regret for the RP component of treatment compared to radiotherapy (16.9% vs 4.2%, P = 0.01). DR for androgen deprivation was 14.3%. Patients were regretful of surgery due to toxicity, not being adequately informed about radiotherapy as an alternative, positive margins and surgery costs (83%, 33%, 25% and 8% of regretful patients respectively). Toxicity caused DR in the three radiotherapy‐regretful and four ADT‐regretful patients. Patients were twice as regretful overall, and of surgery, for salvage vs adjuvant approaches (both 19.6% vs 10.0%). Conclusion: Decision regret after RP and post‐prostatectomy IG‐IMRT is uncommon, although patients regret RP more than post‐operative IG‐IMRT. This should reassure urologists referring patients for post‐prostatectomy IG‐IMRT, particularly in the immediate adjuvant setting. Other implications include appropriate patient selection for RP (and obtaining clear margins), and ensuring adequately discussing definitive radiotherapy as an alternative to surgery.